Muscle cramping in the marathon: dehydration and electrolyte depletion vs. Muscle damage - Martínez-Navarro, I.; Montoya-Vieco, A.; Collado, E.; Hernando, B.; Panizo, N.; Hernando, C. (The Journal of Strength and Conditioning Research, 2022)
Our aim was to compare dehydration variables, serum electrolytes, and muscle damage serum markers between runners who suffered exercise-associated muscle cramps (EAMC) and runners who did not suffer EAMC in a road marathon. We were also interested in analyzing race pacing and training background. Nighty-eight marathoners took part in the study. Subjects were subjected to a cardiopulmonary exercise test. Before and after the race, blood and urine samples were collected and body mass (BM) was measured. Immediately after the race EAMC were diagnosed. Eighty-eight runners finished the marathon, and 20 of them developed EAMC (24%) during or immediately after the race. Body mass change, post-race urine specific gravity, and serum sodium and potassium concentrations were not different between crampers and noncrampers. Conversely, runners who suffered EAMC exhibited significantly greater post-race creatine kinase (464.17 ± 220.47 vs. 383.04 ± 253.41 UI/L, p = 0.034) and lactate dehydrogenase (LDH) (362.27 ± 72.10 vs. 307.87 ± 52.42 UI/L, p = 0.002). Twenty-four hours post-race also values of both biomarkers were higher among crampers (CK: 2,438.59 ± 2,625.24 vs. 1,166.66 ± 910.71 UI/L, p = 0.014; LDH: 277.05 ± 89.74 vs. 227.07 ± 37.15 UI/L, p = 0.021). The difference in the percentage of runners who included strength conditioning in their race training approached statistical significance (EAMC: 25%, non-EAMC: 47.6%; p = 0.074). Eventually, relative speed between crampers and noncrampers only differed from the 25th km onward (p < 0.05). Therefore, runners who suffered EAMC did not exhibit a greater degree of dehydration and electrolyte depletion after the marathon but displayed significantly higher concentrations of muscle damage biomarkers.